Route of Francisella tularensis infection informs spatiotemporal metabolic reprogramming and inflammation in mice. - Forrest Jessop; Benjamin Schwarz; Eric Bohrnsen; Catharine M Bosio (PLoS ONE)
Route of exposure to pathogens can inform divergent disease pathogenesis and mortality rates. However, the features that contribute to these differences are not well established. Host metabolism has emerged as a critical element governing susceptibility and the metabolism of tissue exposure sites are unique. Therefore, specific metabolic niches may contribute to the course and outcome of infection depending on route of infection. In the current study, we utilized a combination of imaging and systems metabolomics to map the spatiotemporal dynamics of the host response to intranasal (i.n.) or intradermal (i.d.) infection of mice using the bacterium Francisella tularensis subsp tularensis (FTT). FTT causes lethal disease through these infection routes with similar inoculation doses and replication kinetics, which allowed for isolation of host outcomes independent of bacterial burden. We observed metabolic modifications that were both route dependent and independent. Specifically, i.d. infection resulted in early metabolic reprogramming at the site of infection and draining lymph nodes, whereas the lungs and associated draining lymph nodes were refractory to metabolic reprogramming following i.n. infection. Irrespective of exposure route, FTT promoted metabolic changes in systemic organs prior to colonization, and caused massive dysregulation of host metabolism in these tissues prior to onset of morbidity. Preconditioning infection sites towards a more glycolytic and pro-inflammatory state prior to infection exacerbated FTT replication within the lungs but not intradermal tissue. This enhancement of replication in the lungs was associated with the ability of FTT to limit redox imbalance and alter the pentose phosphate pathway. Together, these studies identify central metabolic features of the lung and dermal compartments that contribute to disease progression and identify potential tissue specific targets that may be exploited for novel therapeutic approaches.